2020
DOI: 10.1016/j.amjoto.2020.102535
|View full text |Cite
|
Sign up to set email alerts
|

Early experience in tracheostomy and tracheostomy tube management in Covid-19 patients

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
1
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 7 publications
0
43
1
2
Order By: Relevance
“…Study characteristics are summarized in Table 1. 3,[19][20][21][22] When searching the websites of professional organizations, we found that 3 had produced relevant guidance documents. [13][14][15] Following data extraction and synthesis, the results were categorized according to practice domains for tracheostomy and laryngectomy.…”
Section: Results and Observationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Study characteristics are summarized in Table 1. 3,[19][20][21][22] When searching the websites of professional organizations, we found that 3 had produced relevant guidance documents. [13][14][15] Following data extraction and synthesis, the results were categorized according to practice domains for tracheostomy and laryngectomy.…”
Section: Results and Observationsmentioning
confidence: 99%
“…The main recommendations according to each practice area are shown in Table 2. 3,13,14,[19][20][21][22][23][24][25]…”
Section: Results and Observationsmentioning
confidence: 99%
See 3 more Smart Citations